DINAMIKA KONSELING KELOMPOK DALAM PENGEMBANGAN KOMPETENSI SOSIAL REMAJA - Haniati Gowasa (KOHESI : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze the dynamics of group counseling in developing adolescents’ social competence at SMA Negeri 1 Teluk Dalam. The research employed a qualitative approach using Interpretative Phenomenological Analysis (IPA) to explore students’ subjective experiences in participating in group counseling sessions. Eight students were selected through purposive sampling based on their active involvement in at least six counseling sessions. Data were collected through in-depth interviews, non-participant observations, and documentation of the school counseling program. The analysis involved thematic coding, identification of meaning patterns, and interpretative examination of participants’ lived experiences. The findings indicate that group counseling dynamics significantly contribute to the enhancement of interpersonal communication skills, empathy and social sensitivity, self-confidence, and conflict management abilities. Supportive and reflective group interactions enable students to learn through direct experience and peer feedback. Group counseling also functions as a safe social learning environment that fosters emotional regulation and mature social perspective-taking. This study highlights the importance of integrating sustainable group counseling services into school guidance programs as both preventive and developmental strategies to strengthen adolescents’ social competence and character formation.